Politeness Strategies in Indonesian English Textbooks - Ima Frafika Sari (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study investigates the use of politeness strategies in the Bahasa Inggris textbook for Indonesian twelfth-grade students. It aims to identify statements explicitly expressing politeness within the textbook’s conversation exercises. Considering the cultural significance of politeness in Indonesian society, particularly within educational settings, the study highlights the importance of integrating culturally appropriate communication practices into English language teaching (ELT) materials. Employing a descriptive qualitative method, six chapters (Chapters 1, 2, 3, 4, 9, and 14) were analyzed, resulting in 128 instances of politeness strategies. Among these, positive politeness emerged as the most dominant (50%), followed by negative politeness (25%), off-record strategies (11.7%), bald-on-record strategies (7.8%), and “Don’t do the FTA” (5.5%). The findings reveal that the conversational texts reflect Indonesian cultural norms by emphasizing respect, indirectness, and sensitivity to social hierarchy. This research evaluates ELT materials by promoting the integration of linguistically and culturally appropriate politeness strategies. It also encourages educators and textbook developers to prioritize politeness in instructional materials, enhancing students’ pragmatic competence in English communication.